Belanja Daerah, Pertumbuhan Ekonomi dan Kesempatan Kerja di Kota Kupang - Frits O Fanggidae (Jurnal Inovasi Kebijakan, 2019)
Government expenditure is one of the regional fiscal strengths used by regional governments in implementing development. Based on the performance budget principle, every spent must be measured by certain performance. In the economic field, the performance of the government expenditures, among others, is measured by economic growth and employment opportunities. This study uses 3 (three) variables, namely employment opportunity (dependent variable), government expenditure (independent variable) and economic growth (intervening variables). By using secondary data (2008-2017) and regression analysis, it was concluded that the government expenditure did not affect employment opportunities through economic growth. This is because the portion of government expenditure for capital expenditure is very small, so it does not lead to the formation of gross fixed capital (infrastructure) and the formation of human capital (technical skills) to encourage economic growth and employment opportunity.